Nationalism in Southeast Asia : 'if the people are with us' - Tarling, Nicholas (RoutledgeCurzon studies in the modern history of Asia, 2004)
Nationalism in Southeast Asia seeks a definition of nationalism through examining its role in the history of Southeast Asia, a region rarely included in general books on the topic.